A Study On Capacity And Physical Supporting Of New Landfill Site In Western Area Of Bojonegoro Regency - Firdausi, Rizal Zubad; Budianto, Agus (SERUNAI, 2021)
Waste has always been a problem in various regions, starting from the village, sub-district, district/city, even in a country level. The rate of population growth is increasing rapidly which has an impact on increasing the amount of waste. The Landfill for waste in Bojonegoro had been overloaded since 2019, which in 2020 will operate a new Landfill in the western region. Improper planning and inappropriate location of the new Landfill will have a greater negative impact, especially on the surrounding community. The capacity and physical supporting of the landfill are important things that must be considered in planning the development and operation of the landfill, in order to be able to support the activities of using the landfill in a sustainable manner. The purpose of this research was to examine the capacity of the Bojonegoro new Landfill by calculating the capacity of the Bojonegoro New Landfill in serving predictions of waste generation in the future Landfill service area. In addition, this research also analyzed the physical supporting capacity of Bojonegoro new Landfill with a scoring method based on the Landfill feasibility standard. The result of this research was that the Bojonegoro new Landfill was categorized as feasible to operate with the consideration from the results of the analysis that the capacity of the Landfill had a service life of 9 years 7 months which could be categorized as feasible. While the results of the analysis of the physical supporting capacity of the landfill got a total score of 533 with a proper interpretation.